Maternal Parenting Practices in the Prevention of Stunting among Children Under Five: A Scoping Review (Proceedings OPTIMAL, 2025)
Introduction: Stunting remains a critical public health concern, affecting approximately 148 million children globally and contributing to long-term impairments in cognitive development, educational attainment, and economic productivity. Although nutritional interventions have been the traditional focus, increasing evidence underscores the significance of maternal parenting practices—such as responsive caregiving, early stimulation, and nurturing care—in promoting optimal growth and preventing stunting, particularly in low- and middle-income countries (LMICs).Objective: This scoping review aimed to systematically map and synthesize the existing literature on maternal parenting practices associated with the prevention of stunting among children under five in LMICs.Methods: Following the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR reporting standards, a comprehensive search was conducted across five databases (PubMed, Scopus, Web of Science, CINAHL, and PsycINFO) and grey literature sources for studies published between January 2015 and April 2025. Studies were included if they examined maternal behaviors related to stunting prevention in community or household contexts. Data were charted using a standardized form and analyzed thematically.Results: Sixteen studies were included, encompassing diverse designs such as cross-sectional surveys, randomized trials, and cohort studies. Common themes included maternal self-efficacy, education, and responsive caregiving as influential factors in stunting prevention. Interventions integrating behavioral, nutritional, and psychosocial components showed greater effectiveness. However, heterogeneity in methodology and geographic concentration—primarily in Indonesia—was noted.Conclusion: Maternal parenting practices are crucial to stunting prevention and should be embedded in early childhood development policies. Future research should prioritize longitudinal, context-specific interventions to enhance evidence-based programming in LMICs.